Characterization of extracellular vesicles in COVID-19 infection during pregnancy - Dangot, Ayelet; Zavaro, Mor; Bar-Lev, Tali Hana; Bannon, Lian; Zilberman, Ayala; Pickholz, Eliana; Avivi, Irit; Aharon, Anat (Frontiers in Cell and Developmental Biology, 2023)
Abstract Introduction: SARS-CoV-2 infection may cause a severe inflammatory response, inflicting severe morbidity and mortality. This risk is modestly increased in pregnant patients. Despite the hypercoagulability and immunosuppression associated with pregnancy, most pregnant women experience a mild COVID-19 infection. Maternal extracellular vesicles (EVs) may interact with endothelial and immune components to facilitate a favorable disease course. This pilot study aimed to explore the characteristics of EVs released during COVID-19 infection occurring during the third trimester of pregnancy. Methods: In this prospective study, blood samples were obtained from 16 healthy non-pregnant (NP), 18 healthy-pregnant (HP), and 22 COVID-19 positive pregnant subjects (CoV-P). Disease course and pregnancy outcomes were assessed and EVs were characterized. Of note, limited volumes of sample acquired from the subjects made is necessary to use smaller and different subsets of samples for each analysis. Results: The majority (91%) of the COVID-19-pregnant subjects (18 mild and 2 moderate disease) experienced good pregnancy-related outcomes. EV concentrations were higher in healthy-pregnant subjects compared to non-pregnant subjects (p= 0.0041) and lower in COVID-19-pregnant subjects compared to healthy-pregnant subjects (p= 0.0150). CD63 exosome marker expression was higher in EVs of healthy-pregnant subjects and COVID-19-pregnant subjects compared to EVs of non-pregnant subjects (p=0.0149, p=0.0028, respectively). Similar levels of SARS-CoV-2 entry proteins (ACE-2 and TMPRSS2) were found in all three groups. Cytokine content increased in healthy-pregnant subject-EVs compared to non-pregnant EVs, while IL-2 and IL-6 levels were decreased in COVID-19-pregnant subject-EVs compared to healthy-pregnant subject-EVs (p=0.043, p=0.0390, respectively). CD8+, cytotoxic T-cell marker, was lower in non-pregnant EVs compared to healthy-pregnant subject-EVs and to COVID-19-pregnant subjects (p=0.0108, p<0.0001 respectively). COVID-19- pregnant subject-EVs demonstrated higher levels of platelet activation marker (CD62P) than non-pregnant (p=0.0327) and healthy-pregnant subjects (p=0.0365). Endothelial marker EV-CD144+ was lower in healthy-pregnant subjects versus non-pregnant subjects (p= 0.0093), but similar in COVID-19-pregnant and non-pregnant subjects. Other EVs’ coagulation markers/activity, D-Dimer and fibrinogen levels were similar in healthy pregnant subjects and COVID-19 positive pregnant subjects. Conclusions: COVID-19 positive pregnant subjects' EVs demonstrated an attenuated inflammatory response, with no additional activation of the coagulation system.